Product safety failure and restoring reputation across markets: Fonterra's management of the 2013 bacterial contamination crisis - PANG, Augustine (Institutional Knowledge at Singapore Management University, 2017)
Modern distribution systems often stretch beyond national borders such that a highly-visible product failure in a single country may negatively influence the reputation and market share of all identifiable supply chain members-even those that are blameless-in multiple countries, especially when the product is related to food safety. This study considers how Fonterra's response to its 2013 bacterial contamination crisis influenced its own reputation and that of the New Zealand dairy milk industry. It first traces how the crisis started in March 2013 and how it ended in August when investigations showed that the bacteria found did not cause botulism, a fatal disease that attacks the nervous system. It generally appears that Fonterra's initial response was unpersuasive but, over time, it stepped up its crisis management efforts.